2004
DOI: 10.1111/j.1439-0310.2004.01001.x
|View full text |Cite
|
Sign up to set email alerts
|

The Process and Causes of Fledging in a Cavity‐Nesting Passerine Bird, the House Wren (Troglodytes aedon)

Abstract: Little is known about the process or causes of fledging or nest-leaving in passerine birds because researchers can rarely predict when fledging will occur in a given nest. We used continuous videotaping of nests to both document the process of fledging in the house wren, Troglodytes aedon, a small, cavity-nesting songbird, and test hypotheses as to what might cause fledging to begin. Fledging began any time from 14 to 19 d after hatching commenced. Slower-developing broods fledged later than faster-developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
75
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(88 citation statements)
references
References 13 publications
12
75
1
Order By: Relevance
“…It is still not clear whether parents or offspring determine the length of nestling period on the proximate level (Nilsson & Svensson, 1993; Johnsen et al. , 1994; Johnson et al. , 2004), but this analysis shows that there is little potential for adult mortality to drive the evolution of this trait.…”
Section: Discussionmentioning
confidence: 88%
“…It is still not clear whether parents or offspring determine the length of nestling period on the proximate level (Nilsson & Svensson, 1993; Johnsen et al. , 1994; Johnson et al. , 2004), but this analysis shows that there is little potential for adult mortality to drive the evolution of this trait.…”
Section: Discussionmentioning
confidence: 88%
“…Most young fledged during the morning, which could itself be a result of selection for early fledging and is consistent with previous studies of hole‐breeding passerines (Lemel , Nilsson , Johnson et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Studies on fledging have shown that, within broods, fledging order correlates negatively with wing length (Nilsson , Michaud & Leonard , Johnson et al . , Radersma et al . ).…”
mentioning
confidence: 99%
See 2 more Smart Citations